Posterior Cortical Atrophy Presenting with Superior Arcuate Field Defect - Sue Ling Wan; Danuta M. Bukowska; Stephen Ford; Fred K. Chen (Case Reports in Ophthalmological Medicine, 2015)
An 80-year-old female with reading difficulty presented with progressive arcuate field defect despite low intraocular pressure. Over a 5-year period, the field defect evolved into an incongruous homonymous hemianopia and the repeated neuroimaging revealed progressive posterior cortical atrophy. Further neuropsychiatric assessment demonstrated symptoms and signs consistent with Benson’s syndrome.